Opportunities for big data in conservation and sustainability - Rebecca K. Runting (Nature Portfolio, 2020)
Big data reveals new, stark pictures of the state of our environments. It also reveals ‘bright spots’ amongst the broad pattern of decline and—crucially—the key conditions for these cases. Big data analyses could benefit the planet if tightly coupled with ongoing sustainability efforts.